2021
DOI: 10.12659/ajcr.933771
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Tentorial Subdural Hematoma Caused by Traumatic Posterior Cerebral Artery Aneurysm: A Case Report and Literature Review

Abstract: Patient: Male, 42-year-old Final Diagnosis: Traumatic posterior cerebral artery aneurysm Symptoms: Deterioration of mental status and disorientation Medication: — Clinical Procedure: Parent artery occlusion by endovascular approach Specialty: Neurosurgery Objective: Unusual clinical course Background: Subdural hematoma (SDH) caused by traumatic intracranial aneurysm (TICA) is rare. TICAs are known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…This is the first report of a TICA in the distal PCA treated with NBCA [ Table 1 ]. [ 4 , 5 ] Furthermore, only two case reports have reported pseudoaneurysm occurring in the PITA branching from the P3 segment, resulting in ASDH without subarachnoid hemorrhage or cerebral contusion. This was a very rare case of TICA in terms of the rupture mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first report of a TICA in the distal PCA treated with NBCA [ Table 1 ]. [ 4 , 5 ] Furthermore, only two case reports have reported pseudoaneurysm occurring in the PITA branching from the P3 segment, resulting in ASDH without subarachnoid hemorrhage or cerebral contusion. This was a very rare case of TICA in terms of the rupture mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few case studies have reported TICAs in the distal PCA. [ 4 , 5 ] In this study, we report a rare case of a patient with acute subdural hematoma (ASDH) due to a ruptured TICA arising from the distal PCA. The patient was treated by endovascular parent artery occlusion (PAO) using n-butyl-2-cyanoacrylate (NBCA).…”
Section: Introductionmentioning
confidence: 99%